In vivo evidence that truncated trkB.T1 participates in nociception - Leitch Carmen C; Renn Cynthia L; Dorsey Susan G (SAGE Publishing, 2009)
Abstract Brain-Derived Neurotrophic Factor (BDNF) is a central nervous system modulator of nociception. In animal models of chronic pain, BDNF exerts its effects on nociceptive processing by binding to the full-length receptor tropomyosin-related kinase B (trkB.FL) and transducing intracellular signaling to produce nocifensive behaviors. In addition to trkB.FL, the trkB locus also produces a widely-expressed alternatively-spliced truncated isoform, trkB.T1. TrkB.T1 binds BDNF with high affinity; however the unique 11 amino acid intracellular cytoplasmic tail lacks the kinase domain of trkB.FL. Recently, trkB.T1 was shown to be specifically up-regulated in a model of HIV-associated neuropathic pain, potentially implicating trkB.T1 as a modulator of nociception. Here, we report that trkB.T1 mRNA and protein is up-regulated in the spinal dorsal horn at times following antiretroviral drug treatment and hind paw inflammation in which nocifensive behaviors develop. While genetic depletion of trkB.T1 did not affect baseline mechanical and thermal thresholds, the absence of trkB.T1 resulted in significant attenuation of inflammation- and antiretroviral-induced nocifensive behaviors. Our results suggest that trkB.T1 up-regulation following antiretroviral treatment and tissue inflammation participates in the development and maintenance of nocifensive behavior and may represent a novel therapeutic target for pain treatment.